(untitled) (The Pakistan Development Review, 1994)
Economic growth depends largely on growth in agriculture, and agricultural growth is a function of research and development. There is an increasing realisation that the welfare of mankind in the future will hinge crucially on agricultural research policy. The book under review is an edited collection of twelve chapters covering five major themes in the area and is a follow-up volume to the agricultural research indicator series of ISNAR (International Service for National Agricultural Research) published in 1989. The five themes covered are agricultural research in a policy context; measuring agricultural research and economic development; private and public sector agricultural research and emerging issues in the area of agricultural research policy. The list of contributors to this volume reflects the wide experience in the area of international agricultural research that is distilled into the twelve chapters of the book. The international perspective is considerably strengthened by the intimate knowledge of the international agricultural research system with which all three editors and a significant number of the contributors are or have been associated either directly or indirectly.